2021
DOI: 10.1007/s10212-021-00538-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of a teacher-guided comprehension-oriented learning strategy intervention among students in Grade 4

Abstract: Children's development and learning in kindergarten and school. The role of individual characteristics and contextual factors (e.g., teaching practices, parental support) in students' learning. Assessing and supporting learning to learn skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The Word List Memorization Task was used for assessing reported strategy use and perceived strategy effectiveness (see Kikas and Jõgi, 2016;Kikas et al, 2021). First, students were asked to memorize 21 Estonian nouns in Grades 3/4 and 24 Estonian nouns in Grade 9.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Word List Memorization Task was used for assessing reported strategy use and perceived strategy effectiveness (see Kikas and Jõgi, 2016;Kikas et al, 2021). First, students were asked to memorize 21 Estonian nouns in Grades 3/4 and 24 Estonian nouns in Grade 9.…”
Section: Methodsmentioning
confidence: 99%
“…We expected that students who reported using COrLS would show better performance on both word-memorization tasks. Earlier studies have shown that categorization strategies support learning word lists in different age groups (Gaskill and Murphy, 2004;Ornstein et al, 2010;Kikas and Jõgi, 2016;Kikas et al, 2020Kikas et al, , 2021. Still, these relationships may be weak due to utilization deficiency (Bjorklund et al, 1997;Clerc et al, 2014).…”
Section: The Current Studymentioning
confidence: 98%
See 3 more Smart Citations